PENGARUH SITUATION-BASED LEARNING DAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KEMAMPUAN PROBLEM POSING SISWA PADA MATERI PERISTIWA ALAM - Jayadinata, Asep Kurnia; Isrok'atun, Isrok'atun (Jurnal Pena Ilmiah, 2019)
The purpose of this study was to find out how the effect of learning using the SBL model on the ability of problem posing, how the influence of learning using the CTL model on problem posing abilities, and how the difference in influence between learning using the SBL model and learning using the CTL model on students' problem posing abilities material for natural events. The instruments used in this study were problem posing ability test questions, attitude scale questionnaires, teacher performance observation sheets and student activities and field notes. The research method used was a quasi experiment with nonequivalent control group design. The population of the study was all fifth grade elementary school students in Situraja Subdistrict. Sampling used is a random technique. While the research samples were SD Warungketan as the experimental class and SDN Ambit as the control class. The results showed that there was no difference between learning using the SBL model and learning using the CTL model on students' problem posing abilities. Both models have a positive influence and each has increased. The other findings are that students give a positive response to learning using the SBL model.